Studying anti-Semitism using primary sources in graphic novels. Issue 1 (1st July 2020) - Reingold, Matt
Recent trends in history education have emphasized the study of primary sources as an important conduit for fostering critical and historical thinking skills and for allowing students to assume the role of historians. In the following article, I examine the ways that Nora Krug's Belonging, Ari Folman and David Polonsky's Anne Frank's Diary and Will Eisner's The Plot, all meaningfully engage with primary sources as a central feature of the graphic novel. Each of the texts addresses a different aspect of historical anti-Semitism but through the use of visual and textual devices that are woven into the primary sources, connections to contemporary society abound. Furthermore, what also emerges with these three texts is an active engagement with the reader wherein the primary sources are used to demand that the reader thinks about historical and contemporary anti-Semitism. Therefore, these three texts do not simply include primary sources but, like effective history educators, they model and foster critical and historical thinking through the visual and textual prompts. Their inclusion turns the reader into an active historian who participates in the process of discovery and arrives at their own understanding of the perniciousness of anti-Semitism throughout history and its continued presence in their own communities.